20‐4: High‐Performance and Low‐Power Full Color Reflective LCD for New Applications. Issue 1 (29th May 2019) - Hakoi, Hiroyuki; Ni, Ming; Hashimoto, Junichi; Sato, Takashi; Shimada, Shinji; Minoura, Kiyoshi; Itoh, Akiko; Tanaka, Kohei; Matsukizono, Hiroshi; Otsubo, Masashi
Abstract : We have developed a reflective LCD with full color video image and low power consumption. By combining a new twisted VA‐LC mode, a silver alloy electrode with micro reflective structure (MRS), and IGZO‐TFT technology, a 22‐inch prototype has achieved excellent optical properties and flicker‐less 1Hz driving.